Image fusion of mass spectrometry and microscopy: a multimodality paradigm for molecular tissue mapping - Van de Plas, Raf; Yang, Junhai; Spraggins, Jeffrey; Caprioli, Richard M (Nature methods, 2015)
An approach to fuse images from imaging mass spectrometry and microscopy provides biological insights into molecular tissue distributions beyond what can be obtained from either modality individually. We describe a predictive imaging modality created by 'fusing' two distinct technologies: imaging mass spectrometry (IMS) and microscopy. IMS-generated molecular maps, rich in chemical information but having coarse spatial resolution, are combined with optical microscopy maps, which have relatively low chemical specificity but high spatial information. The resulting images combine the advantages of both technologies, enabling prediction of a molecular distribution both at high spatial resolution and with high chemical specificity. Multivariate regression is used to model variables in one technology, using variables from the other technology. We demonstrate the potential of image fusion through several applications: (i) 'sharpening' of IMS images, which uses microscopy measurements to predict ion distributions at a spatial resolution that exceeds that of measured ion images by ten times or more; (ii) prediction of ion distributions in tissue areas that were not measured by IMS; and (iii) enrichment of biological signals and attenuation of instrumental artifacts, revealing insights not easily extracted from either microscopy or IMS individually.